Unveiling the potential: Patient-derived organoids in cancer research and treatment - Zhan Wang (Oral Oncology Reports)
Patient-derived organoids (PDOs) represent a cutting-edge approach in cancer research that holds significant promise for revolutionizing various aspects of oncology. These three-dimensional structures, cultivated from patient tumor samples, faithfully mimic the intricate cellular composition and architecture of the original tumors. Unlike traditional cell cultures, PDOs retain the heterogeneity and complexity of the tumor microenvironment, making them invaluable tools for studying cancer biology, disease progression, and therapeutic responses. Overall, PDOs represent a transformative technology in cancer research, offering unprecedented opportunities to unravel the complexities of the disease and develop more effective personalized treatment strategies. As the field continues to advance, organoid models are poised to play an increasingly prominent role in driving innovation and improving patient care in oncology.